Development of standardized achievement tests for BRAC NFPE Schools - Latif, A. H.; Haq, Muhammad Nazmul; Arzoo, Mir Jahan Ara; Akter, Shaheen; Hasan, Monira (BRAC Research and Evaluation Division (RED), 2019)
Measurement of learners' achievement in schools continues to be a great concern to educational administrators, teachers and guardians. Learner's status in the school, his/her future endeavors and many other personal attributes depend on achievements in school examinations. Though examination is a crucial factor in the formal education system it is not presently seen as an important clement in BRAC's NFPE programme. Learners once admitted to the NFPE school are expected . to complete the three year course unless one is dropped or moved out. Teachers rate their learners regularly in the class and provide remedial measures should it be necessary. This is the common approach in the non formal system but it does not provide indicators . that accurately measure students' cognitive performance and skills. After completion of NFPE schooling, most of the learners arc expected to enter into the government primary schools either in grade IV or V depending on the result of some sort of admission test. As BRAC's NFPE programme includes quality inputs, the standard of output, ie., the learners' achievements are expected to be of high quality. That is why, it is all the more necessary that the NFPE graduates should be evaluated in reference to particular achievement criteria ie., test scores, so that necessary measures can be taken and changes required are incorporated in the programme for ensuring the quality set' for it.